Ռամկավարների գործունէութիւնը Կիլիկիայում (1918—1920 թթ.) - Սարգսեան, Սուրէն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
История нового и новейшего периода Киликии и, в частности, деятельности традиционных армянских партий мало изучена. Армяне Киликии, пережившие ужасы геноцида, поверив обещаниям оккупировавших их край французов, после окончания Первой мировой войны начали возвращаться и восстанавливать свои очаги. Армянские партии также начали возвращаться с людьми. Однако, чтобы как можно скорее стать хозяином побед, между ними начались межпартийные усобицы. Во всех вопросах постоянно сотрудничали рамкавары и реорганизованные гнчакяны. Постепенно они увеличили свои местные структуры и основали новые клубы, провели плодотворную работу и добились значительных успехов в экономике, образовательно-культурной и военной сферах. Однако французы, принявшие протурецкую политику, вскоре покинули Киликию. За ними последовали также армяне Киликии и, естественно, армянские партии. The history of the new and modern period of Cilicia and, in particular, the activities of the traditional Armenian parties have been little studied. The Armenians of Cilicia, who survived the horrors of genocide, believing the promises of the French who occupied their region, began to return and restore their homes after the end of World War I. The Armenian parties also began to return with their people. However, to win a victory as soon as possible, inter-party misunderstandings began between them. The Ramgavars and reorganized Hunchakians constantly cooperated in all matters. Gradually, they enlarged their local structures and founded new clubs, carried out fruitful work and achieved significant success in the economical, educational, cultural and military spheres. However, the French, who adopted a pro-Turkish policy, soon left Cilicia. They were followed by the Armenians of Cilicia and, of course, the Armenian parties.
Keywords: Պատմութիւն